2017
DOI: 10.3390/nano7010007
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Surfaces Coated with Triangular Silver Nanoplates: Antibacterial Action Based on Silver Release and Photo-Thermal Effect

Abstract: A layer of silver nanoplates, specifically synthesized with the desired localized surface plasmon resonance (LSPR) features, was grafted on amino-functionalized bulk glass surfaces to impart a double antibacterial action: (i) the well-known, long-term antibacterial effect based on the release of Ag+; (ii) an “on demand” action which can be switched on by the use of photo-thermal properties of silver nano-objects. Irradiation of these samples with a laser having a wavelength falling into the so called “therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 40 publications
5
78
0
1
Order By: Relevance
“…We used the standard LbL approach to graft large AgNTR (size ca. 170 nm) on a glass surface bearing a PEI‐silane layer, dipping the surfaces in a AgNTR colloidal solution . Surface Ag concentration was 1.87 µg Ag/cm 2 , a value between those found for AgNP and AgNPLT surfaces (Table ) and Ag + release (48 h) was significant on an absolute scale (0.075 µg Ag/cm 2 ) although low with respect to total Ag (4 %).…”
Section: Switchable Antibacterial Surfacesmentioning
confidence: 81%
“…We used the standard LbL approach to graft large AgNTR (size ca. 170 nm) on a glass surface bearing a PEI‐silane layer, dipping the surfaces in a AgNTR colloidal solution . Surface Ag concentration was 1.87 µg Ag/cm 2 , a value between those found for AgNP and AgNPLT surfaces (Table ) and Ag + release (48 h) was significant on an absolute scale (0.075 µg Ag/cm 2 ) although low with respect to total Ag (4 %).…”
Section: Switchable Antibacterial Surfacesmentioning
confidence: 81%
“…[ 71,220,221 ] This absorbed energy can be dissipated either by re‐emitting a photon, or via heat through electron–electron interactions and then electron–phonon relaxation, which induces vibrations in the metal lattice structures, these lattice vibrations are transferred into thermal energy causing localized heat around the nanomaterial [ 44,71,220 ] ( Figure ). This phenomenon has been predominately studied using gold; however silver, [ 222 ] copper, [ 223 ] and other materials [ 224 ] have also been investigated. By conjugating specific attachments to the nanomaterials, such as antibodies, they can specifically target the pathogen of interest, where the localized increase in temperature causes cell death through a suite of actions including denaturation of essential proteins/enzymes, induction of heat shock proteins, disruption of metabolic signaling and rupture of the cell membrane [ 71,85,218,219,225–227 ] (Figure 10).…”
Section: Light‐activated Antimicrobial Metal Nanomaterialsmentioning
confidence: 99%
“…[ 223 ] Additionally, D'Agostino et al utilized triangular silver nanoplates, with sides approximately 200 nm, which demonstrated inactivation of S. aureus (97%) and E. coli (>99%) cells respectively, following irradiation at 808 nm (260 mW cm −2 ), for 15 min. [ 222 ] Interestingly, they were able to affix the nanoplates to glass surfaces to demonstrate the effectiveness of photothermal nanomaterials as a stimuli‐activated surface coating, for purposes such as biomedical implants. [ 222 ] Furthermore, they explored the relationship between the nanoscale dimensions of the triangular nanoplates and the specific excitation wavelength to initiate the photothermal response, highlighting the controllability of this technique, which will logically become easier to manipulate as synthesis processes of metal nanomaterials continue to rapidly improve.…”
Section: Light‐activated Antimicrobial Metal Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The laser-induced hyperthermia almost completely eliminated bacteria S. aureus and E. coli [50]. Moreover, bulk glass surfaces coated with polymer with synthesized citrate silver nanoplates have ability to strongly absorb laser radiation in the near infrared (NIR) range and this coating exerts an antibacterial activity against S. aureus and E. coli [51]. The mechanism of action of these composites are still under debate but they rely on release of silver ions from nano-objects and the subsequent interaction of Ag with bacteria and the antibacterial action caused by photothermal effect [50,51].…”
Section: Polymer Stabilized Nanomaterialsmentioning
confidence: 99%